2020
DOI: 10.1080/15592324.2020.1856547
|View full text |Cite
|
Sign up to set email alerts
|

Constriction of endoplasmic reticulum tubules by the viral movement protein BMB2 is associated with local BMB2 anchorage at constriction sites

Abstract: Plant virus-encoded movement proteins (MPs) interact with endoplasmic reticulum (ER) membranes, the cytoskeleton, and plasmodesmata (PD) to mediate intracellular delivery of the virus genome to PD and its further transport through PD from infected to healthy cells.The Hibiscus green spot virus MP termed BMB2 has been shown to induce constrictions of ER tubules and to occur at highly curved membranes, thus showing properties similar to those of reticulons, a class of cellular proteins inducing membrane curvatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The data presented in this paper demonstrate that BMB2-induced PAMBs have a complex internal structure. Previous studies have shown that (1) PAMBs are composed of ER-derived membranes containing BMB2, and (2) BMB2 can induce constrictions of cortical ER tubules [ 23 , 24 , 46 ]. Based on these data, one might expect that PAMBs can be formed from constricted ER tubules.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented in this paper demonstrate that BMB2-induced PAMBs have a complex internal structure. Previous studies have shown that (1) PAMBs are composed of ER-derived membranes containing BMB2, and (2) BMB2 can induce constrictions of cortical ER tubules [ 23 , 24 , 46 ]. Based on these data, one might expect that PAMBs can be formed from constricted ER tubules.…”
Section: Discussionmentioning
confidence: 99%
“…Because the complementation assays with the ORFs 2-3, termed BMB1 and BMB2, were performed in the absence of any other higrevirus-encoded protein, it is thought that the BMB machinery transport vRNPs, at least in the PVX model system (59) the cytoplasm and the nucleoplasm, and likely participates in the formation of vRNPs. BMB2 is an integral membrane protein that induces constrictions of the ER tubules, similar to reticulons (56,57,59). The intracellular transport of BMB2 to PD can occur via lateral translocation along the ER membranes (58).…”
Section: Cell-to-cell Movement Of Kitavirusesmentioning
confidence: 99%